Horizontal propagation of large‐amplitude mountain waves into the polar night jet. Issue 3 (2nd February 2017) - Ehard, Benedikt; Kaifler, Bernd; Dörnbrack, Andreas; Preusse, Peter; Eckermann, Stephen D.; Bramberger, Martina; Gisinger, Sonja; Kaifler, Natalie; Liley, Ben; Wagner, Johannes; Rapp, Markus
Abstract: We analyze a large‐amplitude mountain wave event, which was observed by a ground‐based lidar above New Zealand between 31 July and 1 August 2014. Besides the lidar observations, European Centre for Medium‐Range Weather Forecasts (ECMWF) data, satellite observations, and ray tracing simulations are utilized in this study. It is found that the propagation of mountain waves into the middle atmosphere is influenced by two different processes at different stages of the event. At the beginning of the event, instabilities in a weak wind layer cause wave breaking in the lower stratosphere. During the course of the event the mountain waves propagate to higher altitudes and are refracted southward toward the polar night jet due to the strong meridional shear of the zonal wind. As the waves propagate out of the observational volume, the ground‐based lidar observes no mountain waves in the mesosphere. Ray tracing simulations indicate that the mountain waves propagated to mesospheric altitudes south of New Zealand where the polar night jet advected the waves eastward. These results underline the importance of considering horizontal propagation of gravity waves, e.g., when analyzing locally confined observations of gravity waves. Key Points: Analysis of a large‐amplitude mountain wave event above New Zealand Vertical propagation of mountain waves in the lower stratosphere is attenuated by instabilities Mountain waves are refracted in the upper stratosphere and propagate toward the polar night jet